Peran Syukur sebagai Moderator Pengaruh Perbandingan Sosial terhadap Self-esteem pada Remaja Pengguna Media Sosial - Johan Satria Putra (Psikohumaniora: Jurnal Penelitian Psikologi, 2018)
Adolescents consistently compare themselves with others they see on social media. This habit can bring up in them a sense of envy or inferiority, which then can lead to a decrease in self-esteem. Therefore, it is necessary to have aspects that can increase their confidence and optimism, including in term of spirituality, their sense of gratitude. The purpose of this study was to see the role of gratitude as moderating variable in the influence of social comparison on the self-esteem of social media adolescent users. The research was conducted using social comparison scale of Iowa-Netherlands Comparison Orientation Scale (INCOM), gratitude scale, and self-esteem state scale, which were distributed to 200 social media adolescent users in DKI Jakarta, were involved through incidental sampling. The results of data analysis showed that there was a significant role of gratitude in influencing social comparison to change these participants’ self-esteem. The sense of gratitude served to increase these adolescents’ self-esteem, which previously decreased as a result of social comparison. This study had a number of weaknesses in the use of the instruments, especially the social comparison scale. Any similar study in the future is expected to focus more on one kind of social media.